Effectiveness of various human papillomavirus vaccination strategies: A community randomized trial in Finland. (27th September 2021) - Lehtinen, Matti; Apter, Dan; Eriksson, Tiina; Harjula, Katja; Hokkanen, Mari; Natunen, Kari; Nieminen, Pekka; Paavonen, Jorma; Palmroth, Johanna; Petäjä, Tiina; Pukkala, Eero; Vänskä, Simopekka; et al.
Abstract: Introduction: We conducted a community‐randomized trial (NCTBLINDED) in Finland to assess gender‐neutral and girls‐only vaccination strategies with the AS04‐adjuvanted human papillomavirus (HPV)‐16/18 (AS04‐HPV‐16/18)vaccine. Methods: Girls and boys (12−15 years) were invited. We randomized 33 communities (1:1:1 ratio): Arm A: 90% of randomly selected girls and boys received AS04‐HPV‐16/18 vaccine and 10% received hepatitis B vaccine (HBV); Arm B: 90% of randomly selected girls received AS04‐HPV‐16/18 vaccine, 10% of girls received HBV, and all boys received HBV; Arm C: all participants received HBV. Effectiveness measurements against prevalence of HPV‐16/18 cervical infection were estimated in girls at 18.5 years. The main measures were: (1) overall effectiveness comparing Arms A or B, regardless of vaccination status, vs Arm C; (2) total effectiveness comparing AS04‐HPV‐16/18 vaccinated girls in pooled Arms A/B vs Arm C; (3) indirect effectiveness (herd effect) comparing girls receiving HBV or unvaccinated in Arm A vs Arm C. Co‐primary objectives were overall effectiveness following gender‐neutral or girls‐only vaccination. Results: Of 80, 272 adolescents invited, 34, 412 were enrolled. Overall effectiveness was 23.8% (95% confidence interval: −19.0, 51.1; P  = 0.232) with gender‐neutral vaccination. Following girls‐only vaccination, overall effectiveness was 49.6% (20.1, 68.2; P  = 0.004). Total effectiveness was over 90% regardless of vaccination strategy. No herd effect was found. Immunogenicity of the AS04‐HPV‐16/18 vaccine was high in both sexes. Conclusions: This study illustrates the difficulty in conducting community randomized trials. It is not plausible that vaccinating boys would reduce overall effectiveness, and the apparent lack of herd effect was unexpected given findings from other studies. This analysis was likely confounded by several factors but confirms the vaccine's high total effectiveness as in clinical trials. Abstract : This community randomized trial evaluating two HPV vaccination strategies (girls only and gender neutral) in Finland failed to show indirect benefit for girls by vaccinating boys. Several factors might have prevented to show herd effect such as randomization bias. However, the study confirms the high total effectiveness of the vaccine in girls.